Development and characterization of genomic SSR markers for Anneslea fragrans (Pentaphylacaceae)1. (26th October 2017) - Sun, Lijing; Meng, Kaikai; Liao, Boyong; Li, Chunmei; Zhang, Yue; Liao, Wenbo; Chen, Sufang
Abstract : Premise of the study: The genus Anneslea (Pentaphylacaceae) contains four species and six varieties, most of which are locally endemic. Here, simple sequence repeat (SSR) markers were developed for the conservation of these species. Methods and Results: The genome of A. fragrans was sequenced and de novo assembled into 445, 162 contigs, of which 30, 409 SSR loci were detected. Primers for 100 SSR loci were validated with PCR amplification in three populations of A. fragrans . Seventy‐nine loci successfully amplified, and 30 were polymorphic. The mean number of alleles, observed heterozygosity, and expected heterozygosity were 7.01 ± 1.60, 0.817 ± 0.241, and 0.796 ± 0.145, respectively. Most primers could be amplified in Ternstroemia gymnanthera, T. kwangtungensis, and Cleyera pachyphylla . Conclusions: Our study demonstrated that shotgun genome sequencing is an efficient way to develop genomic SSR markers for nonmodel species. These genomic SSR loci will be valuable in population genetic studies in Anneslea and its relatives.